Political theories of decolonization postcolonialism and the problem of foundations - Kohn, Margaret; McBride, Keally D. (New York ; Oxford : Oxford University Press, 2011)
Recent scholarship in political theory has focused on the treatment of colonialism in the writings of canonical thinkers such as Locke, Burke, Mill, Diderot, Tocqueville, Smith, and Kant, revealing the extent to which the subject of colonialism and imperialism dominated the minds of great thinkers as the colonial project took place.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Decolonization; Postcolonialism